Brassinosteroids positively modulate growth: Physiological, biochemical and anatomical evidences using two tomato genotypes contrasting to dwarfism - MAIA, Camille Ferreira (2018)
Ministério da Educação, Universidade Federal Rural da Amazônia e Programa de Pós-Graduação em Agronomia